2005
DOI: 10.1002/chin.200525096
|View full text |Cite
|
Sign up to set email alerts
|

Human Immunodeficiency Virus‐Reverse Transcriptase Inhibition and Hepatitis C Virus RNA‐Dependent RNA Polymerase Inhibition Activities of Fullerene Derivatives.

Abstract: Derivatives. -(MASHINO*, T.; SHIMOTOHNO, K.; IKEGAMI, N.; NISHIKAWA, D.; OKUDA, K.; TAKAHASHI, K.; NAKAMURA, S.; MOCHIZUKI, M.; Bioorg. Med. Chem. Lett. 15 (2005) 4, 1107-1109; Kyoritsu Coll. Pharm., Minato, Tokyo 105, Japan; Eng.) -A. Forchert 25-096

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(38 citation statements)
references
References 1 publication
0
38
0
Order By: Relevance
“…We report here, for the first time, HCV-RdRp-inhibitory activity of demethylzeylasteral (compound 5) from T. hypoglaucum. Due to HCV-RdRp-inhibitory activity of compound 5 and based on the previous research showing increased HCV-RdRp-inhibitory activity following alteration of functional groups in synthesized compounds [28], additional modification of the functional groups R1, R2, R3, and R4 (see Fig. 1) of compound 5 for leading to more potent HCV-RdRp-inhibitory substances would be a valuable step toward finding anti-HCV agents based on natural products.…”
Section: Discussionmentioning
confidence: 99%
“…We report here, for the first time, HCV-RdRp-inhibitory activity of demethylzeylasteral (compound 5) from T. hypoglaucum. Due to HCV-RdRp-inhibitory activity of compound 5 and based on the previous research showing increased HCV-RdRp-inhibitory activity following alteration of functional groups in synthesized compounds [28], additional modification of the functional groups R1, R2, R3, and R4 (see Fig. 1) of compound 5 for leading to more potent HCV-RdRp-inhibitory substances would be a valuable step toward finding anti-HCV agents based on natural products.…”
Section: Discussionmentioning
confidence: 99%
“…Results indicated that the amino acid modified fullerenes strongly inhibited HIV-RT with the IC 50 of 0.029 M [38]. A series of C 60 derivatives were synthesized, and the inhibition efficiency of fullerene to HIV-1 strain was improved with the increased positive charges near to the C 60 backbone [39].…”
Section: Anti-virus Activitymentioning
confidence: 98%
“…C 60 didn't possess a specific affinity to the virions and it seemed that ROS was contributed for it [44]. Hepatitis C virus (HCV) inhibition effects of three fullerenes derivatives were not significantly different [38].…”
Section: Anti-virus Activitymentioning
confidence: 99%
“…However, much potential research and many applications in biological systems are greatly hindered because the unique cage structure of fullerene made it highly hydrophobic and hardly soluble in hydrophilic solvents. The water-solubility of fullerene and its derivatives has been improved in several ways, including: (1) chemical functionization to obtain soluble derivatives [4] ; (2) utilization of stabilizer to make aqueous solution [5,6] ; (3) formation of a uniform dispersion of aqueous nanoparticle suspension by a specific procedure which includes dissolving fullerene or its derivative in some organic solvents (e.g., tetrahydrofuran and toluene), mixing with water, and finally removing organic solvents [7,8] .…”
Section: Introductionmentioning
confidence: 99%